Design of an Early Warning System-Based Information System for Cash Advance Requests - Neli Yuliani; Annisa Yuniar Larasati (Universitas KH. Abdul Chalim Mojokerto, 2026)
The West Java Provincial Department of Industry and Trade faces challenges in managing Cash Advances (Uang Persediaan/UP) because the process is still manual and paper-based. This condition results in the absence of early warnings for potential breaches of budget ceilings and quarterly Cash Disbursement Plans (RPD), bottlenecks in accountability reporting, limited real time monitoring, risks of human error, and weak document traceability that may lead to audit findings related to the Internal Control System (SPI). This study aims to design an Early Warning System (EWS) based information system for UP submissions in accordance with Government Regulation No. 12 of 2019 and Minister of Home Affairs Regulation No. 77 of 2020. The research employs a qualitative case study approach, with system development using the Waterfall model. Data were collected through observation, interviews, documentation review, and workflow analysis. The system is built on Google Workspace and includes EWS validation and automated notifications, a centralized database to ensure data consistency, a monitoring dashboard, and an integrated digital approval workflow. The design results in an architecture, functional requirements, and technical specifications that significantly reduce administrative processing time, enhance transparency and accountability, strengthen controls, and reduce the risk of overspending and audit findings.